2009
DOI: 10.1002/j.2051-3909.2009.tb00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapist‐led weekly patient treatment reviews

Abstract: The purpose of this discussion article is to explore the implementation of radiation therapist‐led treatment reviews as a form of advanced practice for radiation therapists in Australia. The feasibility of such a role, the impact on cancer care services and implementation requirements to enable the position to be implemented effectively in an Australian environment are explored. Current practice involving weekly patient treatment reviews and cases where health professionals other than radiation oncologists hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Despite interest shown in an AP model, a review published in 2009 identified a lack of data in Australia identifying or evaluating APRT roles with a further study noting little progress had been made towards formal APRT roles. Further to this, in 2009, Dempsey and Burr noted that radiation therapists were “reluctant to progress the issue of responsibility for higher level plans and treatment…..without the appointment at a senior or advanced practitioner level” .…”
Section: Discussionmentioning
confidence: 99%
“…Despite interest shown in an AP model, a review published in 2009 identified a lack of data in Australia identifying or evaluating APRT roles with a further study noting little progress had been made towards formal APRT roles. Further to this, in 2009, Dempsey and Burr noted that radiation therapists were “reluctant to progress the issue of responsibility for higher level plans and treatment…..without the appointment at a senior or advanced practitioner level” .…”
Section: Discussionmentioning
confidence: 99%
“…With much initial work done in the United Kingdom, RT participation in review clinics has been in practice since at least 2000 in some parts of the world in the context of the development of advanced practice models. Reported benefits include increased communication, decreased patient waiting times, and more consistent patient monitoring and management . RO time and workload is saved and can be utilized to assess more complex patients or to perform other higher level duties.…”
Section: Introductionmentioning
confidence: 99%
“…The increased role for RTs has potential advantages of improved job satisfaction and better recruitment and retention . Data have shown that some patients present to clinics with minimal treatment‐related sequelae, resulting in a low medical intervention (MI) rate occurring in clinics . This low need for MI further enables RT participation …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations